2006
DOI: 10.3122/jabfm.19.2.191
|View full text |Cite
|
Sign up to set email alerts
|

Copper Deficiency as Cause of Unexplained Hematologic and Neurologic Deficits in Patient with Prior Gastrointestinal Surgery

Abstract: Copper is a trace mineral essential to hematopoiesis and to the structure and function of the nervous system. Copper deficiency is a rare cause of anemia, leukopenia, and myeloneuropathy, but should be considered in the differential diagnosis in a patient with prior gastrointestinal surgery. We report the case of a 51-year-old woman admitted for nonspecific neurologic symptoms ultimately found to be due to copper malabsorption. Case ReportsA 51-year-old female presented to the emergency department complaining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
8

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 21 publications
(14 reference statements)
0
32
0
8
Order By: Relevance
“…Some investigators have already reported copper deficiency with symptoms after non-bariatric gastrectomy [23][24][25] . Such patients presented with hematological or neurological symptoms, usually many years after the operations (5-21 years).…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators have already reported copper deficiency with symptoms after non-bariatric gastrectomy [23][24][25] . Such patients presented with hematological or neurological symptoms, usually many years after the operations (5-21 years).…”
Section: Discussionmentioning
confidence: 99%
“…Relatively few cases of Cu deficiency have been reported (for example [160][161][162]), and these are often accompanied by confounding factors such as malnutrition, malabsorption, excessive gastrointestinal losses [152], and excess dietary zinc [163]. Clinically evident Cu deficiency is a relatively infrequent condition that can result in anaemia, compromised immune response and bone abnormalities (including osteoporosis and fractures) [164][165][166].…”
Section: Exposure and Toxicologymentioning
confidence: 99%
“…In particular, copper(II) complexes are known to play a significant role either in naturally occurring biological systems or as pharmacological agents [1][2][3][4][5]. As a biological element which always combines with protein (or enzyme) to form copper protein (enzyme), copper plays an important role in the hematopoiesis, the central nervous system, and the bone tissue [6][7][8][9][10][11]. Moreover, due to the ability of copper(II) complexes to cleave DNA, many copper(II) complexes were found to be possible medical uses in the treatment of many diseases including cancer [12].…”
Section: Introductionmentioning
confidence: 99%